2016
DOI: 10.3390/rs8020112
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Highly Biodiverse Floodplain Meadow Using Hyperspectral Remote Sensing within a Plant Functional Trait Framework

Abstract: Abstract:We assessed the potential for using optical functional types as effective markers to monitor changes in vegetation in floodplain meadows associated with changes in their local environment. Floodplain meadows are challenging ecosystems for monitoring and conservation because of their highly biodiverse nature. Our aim was to understand and explain spectral differences among key members of floodplain meadows and also characterize differences with respect to functional traits. The study was conducted on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…This is similar to other studies which shows a negative relationship between LDMC and LAI [76]. It was also observed that the moisture content of leaf litter in the forest understory could be estimated by LAI obtained using remotely sensed data due to buffering effect of LAI on the understory microclimate [77].…”
Section: Discussionsupporting
confidence: 76%
“…This is similar to other studies which shows a negative relationship between LDMC and LAI [76]. It was also observed that the moisture content of leaf litter in the forest understory could be estimated by LAI obtained using remotely sensed data due to buffering effect of LAI on the understory microclimate [77].…”
Section: Discussionsupporting
confidence: 76%
“…To characterise the site, we used the Ecological Flora of the British Isles database [35], which contains the ecological traits of species, to acquire Ellenberg's indicator values. These values can be interpreted as follows: species light demand from low to high (1-9); moisture demand from low to high (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12); soil pH from very acid to very alkaline (1-9); and nitrogen demand from the least to excessive (1)(2)(3)(4)(5)(6)(7)(8)(9). These values provide evidence of the environmental niche within which these species are typically found.…”
Section: Experimental Systemmentioning
confidence: 99%
“…It is now possible to create very high-resolution hyperspectral maps of grasslands due to advances in airborne remote sensing, with pixel sizes that are comparable to leaf sizes. Analyses of species-specific leaf and canopy spectra in herbaceous habitats have demonstrated that there is the potential for mapping taxonomic units [4][5][6], phylogenetic groups [7] and plant functional types [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Such integration of prior information has been found to be useful for retrieval of vegetation parameters such as leaf chlorophyll [49,50]. Further insight into this complex issue of dominance of certain parameters in the overall reflectance can potentially be achieved using physically-based radiative transfer models [51]. However, it will require development of conversion equations to relate the pasture quality parameters with those required for the radiative transfer model simulations.…”
Section: Discussionmentioning
confidence: 99%